School Information Management System (SIMS/EMIS) in Lebanon through the Lens of K-12 Public School Leaders: A Burden or an Opportunity? - Shal, Tarek (Advances in Social Sciences Research Journal, 2022)
The purpose of this paper was to investigate the importance of the Education Management Information System (EMIS) “known as School Information Management System (SIMS)” for the Lebanese public k-12 schools. It is a quantitative study that surveyed the whole population of the K-12 public schools in Lebanon (N=1237[1]). It aimed to determine if SIMS was considered an efficient tool for school principals to improve the quality of learning in their schools. It addressed the multiple technical, human, financial and managerial aspects of SIMS, the different challenges that Lebanese school principals confront while using SIMS. Additionally, it aimed to investigate the improvements school principals suggested and the alternatives they proposed. The study provides recommendations for the Lebanese Ministry of Education and Higher Education on how to improve this application to develop the education sector in Lebanon.